Transistor properties of salen-type metal complexes. Issue 49 (11th August 2020) - Koyama, Kyohei; Iijima, Kodai; Yoo, Dongho; Mori, Takehiko
Abstract : Schiff base complexes exhibit p-channel transistor properties irrespective of metal atoms because the SOMO does not participate in the conduction. Abstract : Schiff base complexes derived from salicylaldehyde and ethylene-, propylene-, and trans -1, 2-cyclohexane-diamines exhibit p-channel transistor properties. The Cu complexes are open-shell compounds, but the oxidation and the hole transport occur at the highest occupied molecular orbital, where the singly occupied molecular orbital (SOMO) does not participate in conduction. Although Ni complexes tend to show larger mobilities than Cu complexes owing to the molecular planarity, the presence of SOMO is not harmful to the transistor properties.